Shading Effects On The Physical Parameter Related To Thermal Comfort In A Hostel Room And Residential House - Zuki, Nurfatin Mohd (Universiti Sains Malaysia, 2021)
External shading systems have been used widely in most tropical buildings to minimise the quantity of solar radiation that enters the structure. Furthermore, by limiting the amount of light levels entering buildings, shading systems dramatically increased daylighting performance. The impact was higher on hotter days, although the shading layers might increase heat generation through the windows. External shading and internal shading are the two types of shading that may be applied. In addition, the internal shading was used to study the physical parameter of thermal comfort toward the shading effect in a room. Several parameters were measured, which is the physical parameters Temperature (T) and Relative Humidity (RH) and also the chemical contaminants Total Volatile Organic Compounds (TVOC) and Particulate Matter (PM10) of Indoor Air Quality. The sampling data of this study were collected in two locations in a hostel room at USM Engineering Campus and a room of a residential house at Bukit Mertajam, Penang. This study showed that the concentrations of the physical parameter (T and RH) in hostel room and residential home in Bukit Mertajam (monitored during the morning, evening and night time), RH was still within the acceptable guideline limit recommended by ICOP when it is in outdoor condition rather than indoor condition. However, the temperature during indoor and outdoor conditions exceeded the permissible guideline limit of 23°C to 26°C. Overall, findings indicated that better thermal comfort occurred at the hostel than at the residential house in Bukit Mertajam. The thermal sensation conditions in the former ranging from ‘Neutral’ to ‘slightly warm’ and ‘slightly warm’ to ‘warm’. Providing adequate ventilation and window shading is a means to maintain good thermal conditions in a room.